Sensitization to Food Additives in Patients with Allergy: A Study Based on Skin Test and Open Oral Challenge - Mozhgan Moghtaderi; Zinatosadat Hejrati; Zahra Dehghani; Faranak Dehghani; Niloofar Kolahi (Iranian Journal of Allergy, Asthma and Immunology, 2016)
There has been a great increase in the consumption of various food additives in recent years. The purpose of this study was to identify the incidence of sensitization to food additives by using skin prick test in patients with allergy and to determine the concordance rate between positive skin tests and oral challenge in hypersensitivity to additives. This cross-sectional study included 125 (female 71, male 54) patients aged 2-76 years with allergy and 100 healthy individuals. Skin tests were performed in both patient and control groups with 25 fresh food additives. Among patients with allergy, 22.4% showed positive skin test at least to one of the applied materials. Skin test was negative to all tested food additives in control group. Oral food challenge was done in 28 patients with positive skin test, in whom 9 patients showed reaction to culprit (Concordance rate=32.1%). The present study suggested that about one-third of allergic patients with positive reaction to food additives showed positive oral challenge; it may be considered the potential utility of skin test to identify the role of food additives in patients with allergy.